Apakah Postur Kerja Berhubungan dengan Kelelahan Kerja? - Linoe, Ribka Gloria; Sumampouw, Oksfriani Jufri; Wowor, Ribka Elisabeth (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2022)
Work postures that are not ergonomic will cause isometric muscle contraction (against resistance) in the main muscles involved in the work. Unnatural posture can cause muscles to not work efficiently, therefore, muscles need more strength to complete their work, which can increase the load that can cause fatigue and strain on muscles and tendons. The purpose of this study was to determine the correlation between work posture and work fatigue on workers at PT. Nusantara Sejahtera Bersama (NSB) Beton Indonesia in Tateli Village, Minahasa Regency. Method: This is a correlational research. This research was conducted at PT. NSB Beton Indonesia Tateli Village, Minahasa Regency in August-December 2021. The respondents of this study were all workers at PT. NSB Beton Indonesia Tateli totaling 32 people. Work posture was measured using the Ovako Working Posture Analysis System (OWAS) Questionnaire. Work fatigue was measured using the Work Fatigue Measurement Tool Questionnaire (KAUPKK). Data analysis was carried out univariately and bivariately. Results: The results showed that the most respondents are aged 16-35 years (62.5%), male (87.5%), high school education (68.8%) and working period > 3 years (65.6%). Furthermore, it was found that the most respondents were in the category of very tired work fatigue (71.9%) and high work posture (56.3%). The results of the cross tabulation show that respondents with high work postures are mostly in the category of very tired work fatigue, as many as 16 respondents, on the other hand, respondents with low work postures have the most low work fatigue as many as 1 respondent. The results of the statistical test obtained a significance value of 0.006 (<0.05), which means that work posture and work fatigue are significantly related. Conclusion: It can be concluded that there was correlation between work posture and work fatigue on workers at PT. NSB Beton Indonesia in Tateli Village, Minahasa Regency. Therefore, workers must work in an ergonomic position and further research needs to be done on other factors that cause work fatigue